2016
DOI: 10.1097/md.0000000000003253
|View full text |Cite
|
Sign up to set email alerts
|

Factors Significantly Associated With the Increased Prevalence of Carotid Atherosclerosis in a Northeast Chinese Middle-aged and Elderly Population

Abstract: Carotid atherosclerosis is associated with many serious cardiovascular diseases; hence, it is necessary to identify factors related to its occurrence in order to develop preventive and therapeutic strategies. This study was conducted to identify risk factors associated with carotid atherosclerosis among the population residing in Northeast China.This epidemiological survey was conducted in a representative group of relatively healthy community residents. All participants answered questions about their medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 37 publications
3
18
1
2
Order By: Relevance
“…Similar to many previous studies,22, 33, 34, 35, 36 we found that traditional risk factors, including older age, male sex, smoking, physical inactivity, hypertension, diabetes mellitus, and dyslipidemia, were significantly associated with CA. Of all risk factors, aging was strongly associated with atherosclerotic lesions 36, 37, 38.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar to many previous studies,22, 33, 34, 35, 36 we found that traditional risk factors, including older age, male sex, smoking, physical inactivity, hypertension, diabetes mellitus, and dyslipidemia, were significantly associated with CA. Of all risk factors, aging was strongly associated with atherosclerotic lesions 36, 37, 38.…”
Section: Discussionsupporting
confidence: 90%
“…Of all risk factors, aging was strongly associated with atherosclerotic lesions 36, 37, 38. Men had a higher prevalence of carotid lesions than women, consistent with previous studies 22, 38. Sex‐related differences might be caused by differential susceptibility to risk factors.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Among them, hypertension is one of the most closely related to CAS [1][2]. Published studies have confirmed that most patients with hypertension have different degrees of CAS [3][4].…”
Section: Introductionmentioning
confidence: 99%